PERANCANGAN MEDIA PEMBELAJARAN E-MODUL MENGGUNAKAN CANVA PADA MATA PELAJARAN TIK KELAS X DI SMA NEGERI 1 HARAU - Rayhan Pratama; Liza Efriyanti; Yunatri Yunatri (Lembaga Pengembangan Kinerja Dosen, 2022)
The rapid development of the digital world today leads teaching staff to be able to utilize technology to help them boost student interest in learning, one way is by designing learning media. For this reason, the Research and Development method is used which uses the 4D development model, namely Define, Design, Develop, and Disseminate. As well as the product test used is the validity test by experts and the effectiveness test by Informatics teachers and students. Launched in 2013, Canva is an online design and publishing tool with a mission to empower people around the world to create any design and publish anywhere. The test results obtained obtained a value of 97% which was stated to be valid and the results of the effectiveness test on students obtained an average of 87.64 which was declared to have high effectiveness. Based on the test results of the modules developed, it can be concluded that learning media using Canva can be used properly and effectively